التفسير العلمي بين المؤيدين والمعارضين - النجار، جمال مصطفى بن عبدالحميد بن عبدالوهاب (جامعة الأزهر - كلية أصول الدين والدعوة بالزقازيق, 2019)
الحمد لله، والصلاة والسلام على رسول الله، وعلى آله وصحبه ومن والاه، وبعد: فهذا بحث بعنوان (التفسير العلمي بين المؤيدين والمعارضين) وهذا البحث يهدف إلى: بيان الرأي الصائب -ولو في نظر الباحث- حول قضية كثر فيها القيل والقال، وكثرة السؤال، ألا وهي قضية تفسير القرآن الكريم بمكتشفات العصر الحديث. وقد تناول الباحث تلك القضية في بحثه هذا من خلال الخطة التالية التي اشتملت على ما يأتي مقدمة: تشتمل على أهمية الموضوع، وخطة تناوله. تمهيد: ويشمل تعريف التفسير العلمي، وقدم اهتمام العلماء به. المبحث الأول: المؤيدون لهذا الاتجاه المبحث الثاني: المعارضون لهذا الاتجاه وأدلتهم المبحث الثالث: الرأي الراجح في هذه القضية الخاتمة، وتشمل أهم النتائج والتوصيات. وكان من أهم النتائج: 1. قدم الاهتمام بالتفسير العلمي، حيث زرعت بذوره أثناء النهضة العلمية في العصر العباسي، ولا زال ينمو حتى خصصت له مراكز عرفت بمراكز الإعجاز العلمي 2- هذا الاتجاه لم يتفق فيه العلماء على كلمة سواء، بل انقسموا إلى فريقين. أ- فريق يؤيد، بحجة أن الله أكثر في قرآنه من الحديث عن الآيات في الأنفس والآفاق، ووجدنا تطابقا بين آياته في كتابه المسطور وفي كونه المنظور. ب- فريق يعارض، بحجة أن تلك العلوم مضطربة، غير قارة، فلا يجوز أن نعرض القرآن لمثل تلك التقلبات والاضطرابات. 3- لا مانع من اقتحام هذا المجال، ولكن بضوابط معلومة، وبقواعد شرعية وعلمية. ثانيا التوصيات 1- قصر البحث في هذا المجال على من رسخت أقدامهم في مجال تفسير القرآن الكريم، ومجال البحث العلم التجريبي، وفق الضوابط والشروط الواردة في هذا البحث. 3- توجيه طلاب مرحلتي الماجستير والدكتوراه توجيها ميدانيا، إلى مراكز الإعجاز العلمي، لتقييم المخرجات التي أنتجتها تلك المراكز، ووضعها تحت منظار النقد والتمحيص.
Thank God, and prayers and peace on the Messenger of Allah, and to his god and his companions, and after: This is a paper entitled "Scientific Interpretation between Supporters and Opponents" This research aims to: to indicate the correct opinion, even in the researcher's opinion, on an issue in which there is a lot of gossip and a lot of question, which is the issue of interpreting the Qur'an with the discoveries of the modern era. The researcher addressed this issue in his research through the following plan that included the following Introduction: Includes the importance of the topic and the plan to address it. Preface: Includes the definition of scientific interpretation, and has given the attention of scientists. The first topic: supporters of this second topic: those opposed to this trend and their evidence The third topic: the most correct opinion in this issue conclusion, and includes the most important results and recommendations. 2- This trend in which the scholars did not agree on a word either, but divided into two teams. (a) A team supports, on the pretext that Allaah is more in his Qur'an than talking about the verses in the selves and horizons, and we found a match between his verses in his book and in his being the perspective. (b) A group that opposes, on the grounds that these sciences are turbulent, non-continental, it is not permissible to expose the Qur'an to such fluctuations and disturbances. 3- There is nothing wrong with breaking into this field, but with known rules and rules of legitimacy and science. Secondly, recommendations 1- limit research in this area to those who have established their feet in the field of interpretation of the Holy Quran, and the field of research experimental science, in accordance with the rules and conditions set out in this research. 3- Directing master's and doctoral students to field orientation, to the centers of scientific miracles, to evaluate the outputs produced by these centers, and to put them under the scope of criticism and scrutiny.
Keywords: القرآن الكريم -- تفسير القرآن -- التفسير العلمي للقرآن -- الإعجاز العلمي